Changing Practice in University English Language Teaching: The Influence of the Chronotope on Teachers' Action. Issue 1 (16th March 2021) - Liddicoat, Anthony J.; Murray, Neil; Zhen, Fengchao; Mosavian, Penny
Abstract: This study aims to investigate how time is coordinated with the professional space of the universities in western China. It examines how the situatedness of English language teachers in institutional spaces influences their understandings of and the value attributed to time and how these impact on how they make changes to their practice following participation in a professional development workshop. Using a combination of observations and interviews, this study identified a preference for adopting teaching techniques that were implemented in less integrated ways and teachers' discussion of change frequently invoked time pressures as a limiting factor in developing their teaching. The study draws on Bakhtin's idea of the chronotope to examine how time is constructed within the space of the university and the ways that such constructions give value to time and how it works as a constraint on teachers changing their practice. It argues that culturally constructed understandings of the status of time in academic work limit what teachers feel able to do in changing their practice and constrain possibilities for change. Abstract :